2013
DOI: 10.1111/jvs.12097
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity: a tool for answering challenging ecological questions

Abstract: Functional trait diversity provides a powerful means of addressing ecology's persistent questions, through its dual role as an indicator of mechanisms driving differences in species composition between communities and as a predictor of ecosystem‐level processes. Functional traits provide a means of testing mechanisms behind species turnover between communities because environmental heterogeneity, competition and disturbance influence species fitness via their traits. Functional traits also provide a link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 21 publications
1
93
0
6
Order By: Relevance
“…Local plant varieties exhibit morphological and functional traits which determine their fitness , enabling adaptation to the harsh climate of drylands and to other disturbances. Moreover, species traits greatly influence ecosystem functions (Mason and de Bello, 2013). It is therefore advisable to promote genetically diverse local provenances in restoration projects, particularly in the context of harsh environmental conditions (Vander Mijnsbrugge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Local plant varieties exhibit morphological and functional traits which determine their fitness , enabling adaptation to the harsh climate of drylands and to other disturbances. Moreover, species traits greatly influence ecosystem functions (Mason and de Bello, 2013). It is therefore advisable to promote genetically diverse local provenances in restoration projects, particularly in the context of harsh environmental conditions (Vander Mijnsbrugge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Question 5 highlights the need for better understanding of the character of ecological tipping points and limits to ES provision across a range of scales (Bommarco et al 2013;Lenton 2013;Mason and De Bello 2013). These transitions, known as thresholds or tipping points, can significantly affect the provision of ES ).…”
Section: Future Research Questions For Bessmentioning
confidence: 99%
“…Further, there is strong evidence of the importance of species functional traits to determine the organization of communities (Petchey & Gaston, 2006;Mason & De Bello, 2013). For instance, studies that analyzed different aspects related to algal biological traits showed that algal life form, adherence, and locomotion are key traits that determine algae response to light (Lange et al, 2011), nutrients (Passy, 2007;Piggott et al, 2012), sediment deposition (Piggott et al, 2012), disturbance (Passy, 2007;Schneck & Melo, 2012), substrate roughness (Schneck et al, 2011b), and dispersal patterns (Wetzel et al, 2012).…”
Section: Introductionmentioning
confidence: 98%